Experimental arteriovenous fistulas: treatment with porous metallic stents. - Geremia, G; Bakon, M; Brennecke, L; Haklin, M (American Journal of Neuroradiology, 1995)
PURPOSE To determine the efficacy of porous metallic stents in the treatment of experimentally created carotid-jugular fistulas. METHODS Carotid-jugular fistulas were constructed surgically in five mongrel dogs. Porous metallic stents were placed endovascularly across the fistula holes within the carotid artery; carotid angiography was performed before, immediately after, and 1 and 2 months after stent placement. The fistula specimens were resected 2 months after stent placement; gross and light microscopic analyses were performed. RESULTS Angiography revealed complete closure of three of the five fistulas 1 month after stent placement; two of the five fistulas remained patent but demonstrated diminished flow rate. All carotid arteries were widely patent throughout the study. Gross pathology of the carotid-jugular specimens revealed fibrous connective tissue and collagen within the fistula hole. A thin layer of endothelium covered the stent wires and the fibrous connective tissue overlying the fistula hole. CONCLUSIONS The stents were effective in closing three of the five fistulas and reducing flow through the fistulas in the remaining animals. With further refinements and variations in technique, porous metallic stents may prove a viable alternative to current endovascular devices for treatment of certain arteriovenous fistulas.